Congruence and party responsiveness in Western Europe in the 21st century. Issue 2 (23rd February 2022) - Ibenskas, Raimondas; Polk, Jonathan
Abstract: Research on party responsiveness in established democracies suggests that parties follow shifts in the preferences of either the general electorate or party supporters. Drawing on theoretical models of party competition and research on party-voter congruence, we argue in this article that in the 21st century Western European mainstream parties respond to their partisan constituents. Parties adjust their policy positions to eliminate previous incongruence between themselves and their constituents and follow the shifts in supporters' positions. Analyses based on a series of datasets that use expert surveys and election surveys to measure parties' positions and several cross-national and national surveys to measure voters' preferences between 1999 and 2014 strongly support the argument that mainstream parties respond to existing incongruence. The findings in this article update many of the empirical results of prior studies on party responsiveness to public opinion shifts, with important ramifications for our understanding of party-based representation in contemporary European democracies.